MENINGKATKAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR NEGERI 11 KOTA KULON GARUT MELALUI MEDIA FLASHCARD - Kartini, Sri Rani; Adiredja, Rajji Koswara; Hakim, Abdul (IPI Press, 2021)
The purpose of this study is to explain the improvement of reading at the beginning of grade 1 elementary school students through flashcard media. The method used is Classroom Action Research. The increase in the initial reading ability of student B's initial ability is 67.50% to 76.44% in the first cycle and 86.35% in the second cycle, so the increase that has been obtained by student B is 18.85%. Student R's initial ability is 66.73% to 76.44% in the first cycle and 86.15% in the second cycle, so the increase that has been obtained by student R is 19.42%. Student F's initial ability is 50.00% to 76.44% in the first cycle and 78.46% in the second cycle, so the increase that has been obtained by student F is 28.46%. it can be concluded that the use of flashcard media can improve the process and results of initial reading skills in grade 1 students of State Elementary School 11 Kulon Garut City, as evidenced by an increase in initial reading ability.